Oromandibular Dystonia: An Update for Dental Professionals - Vidya Ajila; Shruthi Hegde (Cumhuriyet University, 2022)
Oromandibular Dystonia (OMD) is a type of focal dystonia which affects the masticatory, cervical, facial, eyelid, laryngeal, and pharyngeal muscles. OMD patients may consult dentists with involuntary movement or spasm of the lips, tongue, involuntary jaw opening or closing, changes in the occlusion, slurred speech, drooling of saliva, difficulty in mastication, swallowing, and speaking. Due to the uncommon occurrence of OMD, this condition may be misdiagnosed and may lead to unnecessary treatment. Thus thorough knowledge regarding the features of OMD is essential for the dentists. Present review focus on the signs and symptoms of OMD, diagnosis and management of these patients.